The Impact of Phaeomoniella chlamydospora Infection on the Grapevine’s Physiological Response to Water Stress - Part 1 : Zinfandel - Edwards, J.; Salib, S.; Thomson, F.; Pascoe, I.G. (Phytopathologia Mediterranea, 2007)
Phaeomoniella chlamydospora is a vascular pathogen that colonises the xylem tissues of the grapevine. It is associated with Petri disease, which is often considered to be ‘stress-related’. In glasshouse experiments using Zinfandel, stomatal conductance was higher in infected plants, implying that infection interferes with stomatal control. Leaf water potentials were lower in infected plants subjected to water stress, indicating that infection made it more difficult for the vine to get water to the leaf. Clearly, infection alters the grapevine’s physiological response to water stress.